2016
DOI: 10.1111/poms.12550
|View full text |Cite
|
Sign up to set email alerts
|

Donor Reliance on Accounting and its Consequences for the Charitable Distribution Channel

Abstract: T he organization of charitable distribution channels to ensure donor contributions reach beneficiaries in an efficient manner and the use of accounting metrics of such efficiency (whether provided directly or by charity rating groups) are oft-discussed issues in the nonprofit sector. The two issues are inextricably linked since reported efficiency measures influence subsequent donor giving. This study develops a parsimonious model of a charity that must decide how best to employ its resources, either by actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 17 publications
0
9
0
2
Order By: Relevance
“…Accordingly, donation income is the critical resource for nonprofits, and it influences the viability, sustainability, efficiency, and scalability of nonprofit operations (Berenguer & Shen, 2020;Lewis, 2004). Funding concerns contribute to nonprofits' challenges in recruiting quality staff (Wolf, 1999), coordination (Eftekhar et al, 2017), investments in information technology, data collection, and demand forecasting (Berenguer & Shen, 2020), and force them to make myopic decisions (Arya & Mittendorf, 2016;Keshvari Fard et al, 2019). Budget allocation (i.e., the level of spending on programs, fundraising, and administration) is a critical challenge for nonprofits because the reaction of donors to these expenditures is largely unknown.…”
Section: An Operations Management Perspectivementioning
confidence: 99%
“…Accordingly, donation income is the critical resource for nonprofits, and it influences the viability, sustainability, efficiency, and scalability of nonprofit operations (Berenguer & Shen, 2020;Lewis, 2004). Funding concerns contribute to nonprofits' challenges in recruiting quality staff (Wolf, 1999), coordination (Eftekhar et al, 2017), investments in information technology, data collection, and demand forecasting (Berenguer & Shen, 2020), and force them to make myopic decisions (Arya & Mittendorf, 2016;Keshvari Fard et al, 2019). Budget allocation (i.e., the level of spending on programs, fundraising, and administration) is a critical challenge for nonprofits because the reaction of donors to these expenditures is largely unknown.…”
Section: An Operations Management Perspectivementioning
confidence: 99%
“…Alpha and Omega partnered to launch a C-RM campaign centered on one cause product. Alpha's sales and operations planners indicated that they chose the cause product on the basis of the firm's ability to donate excess inventory in exchange for tax incentives, which is common practice (Arya & Mittendorf, 2016;Stecklow, 2005). For each item of the cause product that consumers purchased in-store, Alpha pledged to donate the equivalent (in pounds) to Omega.…”
Section: Empirical Setting the C-rm Campaignmentioning
confidence: 99%
“…Scott () and Hofmann and Reyes () describe the challenges faced by small entrepreneurs in obtaining humanitarian funding through UN agencies. Arya and Mittendorf () investigate the relationships among donors, charities, and beneficiaries. Aflaki and Pedraza‐Martinez () point out that while nonearmarked (unconstrained) funds are most effective in humanitarian operations, they are harder to raise and imply a larger administrative cost per dollar.…”
Section: The Research Nichementioning
confidence: 99%